BIOMECHANICAL ANALYSIS OF THE LEAD STRAIGHT PUNCH ACROSS SKILL LEVELS IN BOXING: A QUANTITATIVE STUDY - Сhulliyеv S.I. (Research Focus International Scientific Journal, 2024)
The article is devoted to the study of the biomechanical analysis of the lead straight punch (jab) across different skill levels in boxing. This study examines novice, intermediate, and elite boxers, focusing on various biomechanical parameters such as punch speed, force, shoulder and torso rotation, hip alignment, and energy transfer. The lead straight punch, or jab, is fundamental in boxing, impacting both offensive and defensive strategies. This study provides an in-depth biomechanical analysis of the lead straight punch among novice, intermediate, and elite boxers using mathematical and statistical methods. Through motion capture and high-speed video analysis, we examine differences in punch speed, force, shoulder and torso rotation, hip alignment, and energy transfer. Our findings, supported by statistical analysis and diagrams, reveal significant variations in biomechanics across skill levels, offering insights for optimizing training programs.